THE EFFECT OF CONVENTIONAL AND SHOCK FREEZING ON DRIP LOSS AND TEXTURAL PARAMETERS OF BEEF MEAT - M. Kral; K. Honzirkova; M. Pospiech; B. Tremlova; M. Zdarsky (Теория и практика переработки мяса, 2016)
Abstract The effect of conventional and shock freezing on thaw drip loss and firmness of beef meat was studied. The meat samples was frozen in conventional freezer at -18 °C and shock frozen meat samples reached -50 °C temperature. Drip loss was measured by weighing the meat sample during thawing. The firmness was performed with TA-XT Plus Texture Analyzer with the volodkevich bite jaws. The firmness score and thaw drip loss differences did not been recognized between conventional and shock freezing meat excluding 7th day.